Fish production, water quality, and the role of nitrification as an ammonia removal process in intensively aerated hybrid catfish ponds - Brian D. Ott; Eugene L. Torrans; Craig S. Tucker (Journal of the World Aquaculture Society)
Abstract Six 0.1‐ha earthen ponds with 45 kW/ha of aeration capacity were stocked with hybrid catfish (Ictalurus punctatus x I. furcatus) ranging from 15,000 to 90,000 fish ha−1 in 15,000 fish ha−1 increments to analyze the effect of nitrogen loading on ammonia accumulation and fish production. Minimum dissolved oxygen (DO) concentration was maintained above 3.0 mg O2 L−1 to prevent hypoxia‐induced appetite reduction. Stocking density did not impact survival but decreased average fish harvest weight and increased food conversion ratio (FCR). Gross production increased with stocking density and ranged from 7249 to 35,674 kg ha−1. Average total (TAN) and un‐ionized ammonia (NH3) were not different among stocking densities despite greater nitrogen inputs in ponds with higher feeding rates. Nitrite (NO2−) and nitrate (NO3−) concentrations were significantly higher in ponds with higher stocking densities, suggesting that nitrification increased with nitrogen loading. Phytoplankton assimilation of ammonia is the primary ammonia removal process in traditional catfish ponds with modest fish densities and feeding rates. However, in intensively aerated ponds with high feeding rates, nitrification can become an important process for ammonia removal. These data indicate that small earthen hybrid catfish ponds with high aeration capacities can increase catfish production without ammonia accumulating.